Letermovir vs. high-dose valacyclovir for cytomegalovirus prophylaxis following haploidentical or mismatched unrelated donor allogeneic hematopoietic cell transplantation receiving post-transplant cyclophosphamide. Issue 8 (3rd July 2022) - Freyer, Craig W.; Carulli, Alison; Gier, Shannon; Ganetsky, Alex; Timlin, Colleen; Schuster, Mindy; Babushok, Daria; Frey, Noelle V.; Gill, Saar I.; Hexner, Elizabeth O.; Luger, Selina M.; Mangan, James K.; et al.
Abstract: Patients undergoing haploidentical or mismatched unrelated donor (haplo/MMUD) allogeneic hematopoietic cell transplantation (alloHCT) receiving post-transplant cyclophosphamide (PTCy) are at high risk of cytomegalovirus (CMV) infection. Experience with letermovir (LET) in this population is limited. This single center retrospective cohort study compared CMV and transplant outcomes between LET and a historical control with high-dose valacyclovir (HDV) prophylaxis in adults undergoing haplo/MMUD alloHCT. Thirty-eight CMV seropositive patients were included, 19 in each arm. LET reduced the incidence of CMV infection (5% vs. 53%, RR 0.01, 95% CI 0.014–0.71, p = .001) and need for CMV treatment by day +100 (5% vs. 37%, RR 0.14, 95% CI 0.18–0.99, p = .017) compared to HDV. Median CMV event-free-survival was improved with LET (not reached vs. 80 days, HR 0.114, 95% CI 0.07–0.61, p = .004). These data support the efficacy of LET in alternative donor transplants.